Strategic Roadmap for Indian Pharmaceutical Industry in the Post 2005 Era - Gaur, Ajai S.; Gaur, Sanjaya S. (Indian Journal of Marketing, 2005)
With less than six months remaining for international patent laws to be implemented in India, many domestic as well as foreign pharmaceutical firms are eagerly waiting to embrace the new challenges as well as opportunities. In spite of a rather small local market, domestic firms have created a definite place for themselves in global pharmaceutical map as cost effective producers of bulk drugs. Introduction of international patent laws in other countries has resulted in phenomenal growth. Indian market, with its large size and very low per capita drug expenditure, provides tremendous potential for foreign players as well as domestic players. The lucrative domestic market, coupled with the easy accessibility of global markets due to liberalization and globalization of Indian pharmaceutical industry (IPI) provides domestic drug manufacturers with definite advantages to face the challenges arising out of the new patent regime. This paper tries to identify the unique features of IPI and suggests a strategic roadmap for domestic firms to successfully tackle the competition and steer their way to growth.